Inside the compassionate organization culture, identity, and image in an English hospice - Baron, Alan; Hassard, John 1953-; Cheetham, Fiona; Sharifi, Sudi (Oxford University Press, 2018)
The focus of this work is care and compassion within the context of organization and management studies. The text aims to understand how members of an English hospice identify or fail to identify with an organization where issues of life and death take centre stage and explores problems it faces regarding its representation in society
Keywords: Organisationskultur; Sterbeklinik; Identität; Image; Management; Großbritannien